Preventive Practices against COVID-19 during the Period of Lockdown in the Eastern Part of Kathmandu - Ghimire, Lata (Journal of Advanced Academic Research, 2020)
A brief study of health seeking behavior was studied in the eastern region of the Kathmandu. 50 respondents were taken in the study. Their knowledge on the pandemic, their views of preventive measures, the practices they are doing and what are the problems they are facing and ultimately the possible way out of the disease was discussed with them taking their view. 50 respondent having equal number of male and female of the indigenous Tamang community were enrolled in the study taking their consent to take part in the study. The majority of the respondents were less educated with low income, thus have to work regularly for their daily essentials. Majority 92 % had stayed in one place and they were aware of the social distance (64%) as well. Regarding the hand washing with the soap and using sanitizer, they were found less serious about it.